Solidification of the Aluminium Alloy in the Mold - Skočilasová, Blanka; Skočilas, Jan (Manufacturing Technology Journal, 2015)
The process of the aluminum alloy casting was investigated. Two materials of the mold were used to observe the effect of thermal conductivity on the time of the solidification. The simulation of the process was conducted in the CFD software respecting the radiation. The results of the designed model of the casting process were compared with the analytical solution obtained from literature.
Keywords: aluminum alloy; simulation; solidification; mold